Stability of soil microbial structure and activity depends on microbial diversity. Issue 2 (2nd December 2013) - Tardy, Vincent; Mathieu, Olivier; Lévêque, Jean; Terrat, Sébastien; Chabbi, Abad; Lemanceau, Philippe; Ranjard, Lionel; Maron, Pierre‐Alain
Summary Despite the central role of microbes in soil processes, empirical evidence concerning the effect of their diversity on soil stability remains controversial. Here, we addressed the ecological insurance hypothesis by examining the stability of microbial communities along a gradient of soil microbial diversity in response to mercury pollution and heat stress. Diversity was manipulated by dilution extinction approach. Structural and functional stabilities of microbial communities were assessed from patterns of genetic structure and soil respiration after the stress. Dilution led to the establishment of a consistent diversity gradient, as revealed by 454 sequencing of ribosomal genes. Diversity stability was enhanced in species‐rich communities whatever the stress whereas functional stability was improved with increasing diversity after heat stress, but not after mercury pollution. This discrepancy implies that the relevance of ecological insurance for soil microbial communities might depend on the type of stress. Our results also suggest that the significance of microbial diversity for soil functional stability might increase with available soil resources. This could have strong repercussions in the current 'global changes' context because it suggests that the combined increased frequencies of extreme climatic events, nutrient loading and biotic exploitation may amplify the functional consequences of diversity decrease.